Association of intrinsic factors with non-contact low back pain among fast bowlers aged between 15-19 years in division 1 boys’ schools in Colombo - Jayasinghe, Udeesh Satheesha; Swaris, Imasha; Weerasooriya, Diluka; Mayura, Dushan; Bandara, Sachinda; Dissanayake, Kavindi; Perera, Angage Dilani Priyashanthi (Asian Journal of Medical Sciences, 2021)
Background: Cricket fast bowlers are identified as the players with a higher risk of injury due to their susceptibility to develop low back pain (LBP). Aims and Objective: This study aims to investigate how intrinsic factors associate with LBP among fast bowlers aged between 15-19 years in Colombo division 1 boys’ schools in Sri Lanka. Materials and Methods: A descriptive cross-sectional study was conducted with one hundred and two (102) fast bowlers who were prospectively monitored over the competition period of 2019 cricket season and the demographic data, severity of LBP, general characteristics and intrinsic factors related data were recorded. Results: Thirty-seven (43.5%) of the subjects were presented with LBP. Reduction of quadriceps strength of dominant side, hamstring strength of non-dominant side and increased ankle dorsiflexion of non-dominant side were found to be significantly associated with non-contact LBP (P<0.05). There were significant differences for the quadriceps strength of dominant side and hamstring strength and ankle dorsiflexion of non-dominant side between the fast bowlers with and without LBP. Conclusion: The results concluded that reduced quadriceps muscle strength of dominant side, reduced hamstring muscle strength and higher ankle dorsiflexion of non-dominant side have an important role in predisposing a fast bowler to have an increase in non-contact LBP.